Simulation of femtosecond pulse in a Kerr-lens mode-locked Ti:sapphire laser - Nomin-Erdene, E; Unurbileg, D; Munkhbaatar, P; Baatarchuluun, Ts; Khos-Ochir, Ts; Munkhbayar, G; Tuvjargal, N; Erdene-Ochir, G; Davaasambuu, J (Scientific transaction of the National University of Mongolia. Physics, 2022)
The Kerr-lens mode-locking (KLM) is known as a suitable method for generation of femtosecond pulses and mode-locked Ti:sapphire laser is now widely used sources of stable, energetic femtosecond pulses. We will present the simulation of KLM in Ti:sapphire laser cavities with a folded-cavity four-mirror by applying the ABCD ray-tracing technique for a Gaussian beam. Simulations will be performed for an asymmetric resonator design. Based on the numerical analysis, we will find the optimum design parameters (slit position, gain cavity spacing, gain medium position) for KLM.